DETERMINING FACTORS OF FIRM VALUE WITH FIRM SIZE AS MODERATING VARIABLE : A STUDY OF BANKING COMPANIES IN INDONESIA - Elsani Fatona Zuanindra; Nawirah Nawirah (Worksheet : Jurnal Akuntansi, 2026)
This study aims to examine the effect of liquidity, funding decisions, investment decisions, and dividend policy on firm value, with firm size as a moderating variable. The sample used in this study were banking companies listed on the Indonesia Stock Exchange (IDX) during the 2022-2025 period. The sampling technique used was Purposive Sampling, and a sample of 17 banks was obtained according to the established criteria, resulting in a total of 68 observations in this study. The data analysis methods used were Panel Data Regression Analysis and Moderated Regression Analysis (MRA). The results of the study indicate that liquidity has no effect on firm value, funding decisions have an effect on firm value, investment decisions have an effect on firm value, dividend policy has no effect on firm value, firm size is unable to moderate the effect of liquidity on firm value, firm size is able to moderate the effect of funding decisions on firm value, firm size is able to moderate the effect of investment decisions on firm value, and firm size is unable to moderate the effect of dividend policy on firm value.